Lung and gut microbiota profiling in intensive care unit patients: a prospective pilot study - Antonios Kritikos; Eric Bernasconi; Yangji Choi; Valentin Scherz; Jean-Luc Pagani; Gilbert Greub; Claire Bertelli; Benoit Guery (BMC Infectious Diseases)
Abstract Background The gut and lung microbiomes play crucial roles in host defense and mayserve as predictive markersfor clinical outcomes in critically ill patients. Despite this, the simultaneous dynamics of lung and gut microbiomes during critical illness remain unclear. This study aims to assess the longitudinal changes in lung and gut microbiota among mechanically ventilated ICU patients with and without infection and to identify microbial features predictive of clinical outcomes, including the development of ventilator associated pneumonia (VAP). Methods In this prospective observational study, we analyzed 73 endotracheal aspirates (ETA) and 93 rectal swabs collected from 38 ICU patients over multiple timepoints (intubation, infection onset, post-antibiotic, and extubation/discharge). Patients were categorized into three groups: (1) VAP, (2) other infections, and (3) uninfected controls. Lung and gut microbiota were characterized using 16S rRNA gene sequencing. Primary outcomes included microbial diversity and community composition; secondary outcomes included ICU length of stay and ventilator-free days. Results Alpha diversity declined more significantly in infected patients than in controls during the ICU stay, with the most pronounced changes in lung microbiota. We found an enrichment of Enterobacteriaceae and other Proteobacteria in the lung microbiome of pneumonia patients, while the gut microbiota remained relatively stable. Relative abundances of key taxa such as Mogibacterium were associated with mechanical ventilation duration. Conclusions This study reveals that distinct microbial patterns in both lung and gut microbiota are associated with infection and clinical outcomes in critically ill patients. Understanding these dynamics is crucial for developing targeted microbiota interventions, potentially improving outcomes such as VAP prevention and management. Trial registration Ethics Committee of Canton Vaud, Switzerland (2017–01820).